Best face forward : why companies must improve their service interfaces with customers - Rayport, Jeffrey F.; Jaworski, Bernard J. (Boston, Mass. : Harvard Business School Press, 2005)
Based on extensive research inside both start-up and established businesses across many industries, Best Face Forward proposes ways that companies can radically reengineer their front-office operations to deploy three types of service interfaces - people-dominant, machine-dominant, and hybrids of the two.This book shows how new roles for technology and people will radically reshape business and competition - and ultimately create a "people-rich" workplace that benefits customers, employees, and shareholders.
Interface as the next frontier of competitive advantage -- The interface imperative -- The front-office revolution -- What people do best -- What machines do best -- Putting the amalgam of people and machines to work -- Managing interface systems -- The interface audit.
Includes bibliographical references ([229]-247) and index.
oif 12/03/15
Loan
Keywords: Customer services -- Management; Service industries -- Technological innovations -- Management; Competition